Autism Spectrum Disorder people and bilingualism - Andrychowicz-Trojanowska, Agnieszka (Neofilolog, 2025)
The aim of the article is to briefly characterise autism spectrum disorder (ASD) and to draw attention to the fact that a large group of ASD people (both children and adults) are exposed to second/foreign language. The goal is also to emphasise the role of scientific knowledge in the fight against popular beliefs and myths related to the negative influence of bi- and multilingualism on the ASD population. Unfortunately, such beliefs are still quite common, also among professionals. The article is comprised of a brief literature review. The majority of the literature is based on present-day studies on ASD bilinguals, although such research is scarce. Hence the article concludes that bi- or multilingualism of ASD children and adults is unavoidable; there is not enough scientific evidence on different aspects of the multilingualism of ASD people, although it is needed; available research evidence clearly shows that exposure to another language is of great importance to people with ASD as it improves, among others, the quality of their lives; there is no scientific evidence on the negative effects of cognitive load or communication problems for ASD people exposed to second/foreign language. On the contrary, it is shown that multilingualism is beneficial for ASDs.